In the midst of plenty : homelessness and what to do about it. - Shinn, Beth (Contemporary Social Issues Ser., 2013)
"Many people helped improve the quality of this book-its accuracy, its clarity, the force of its presentation. Four people were kind enough to read the entire manuscript, and they made helpful comments and corrections throughout: Paul Dornan, formerly responsible for research on homelessness at HUD; Lucie Khadduri, who lives in Olympia WA, a city with a recent upsurge in homelessness; Daniel Perlman, Series Editor for the Society for the Psychological Study of Social Issues, who provided encouragement throughout the book's long gestation period; and Nan Roman, President and CEO of the National Alliance to End Homelessness. Zach Glendening, Molly Richard, and Jason Rodriguez at Vanderbilt University read portions of the manuscript and provided comments that improved clarity and pointed to additional sources of information. Meghan Henry, project director for the Annual Homeless Assessment Reports at Abt Associates, commented extensively on Chapter 1 and confirmed numbers. John Miller, an experienced journalist, also read Chapter 1 and, along with Meghan, helped us make the chapter more readable. Jill's Abt colleagues Anna Jefferson and Hannah Thomas helped identify and expand the vignettes about people experiencing homelessness that begin Chapter 1. Kathryn P. Nelson, who designed HUD's ongoing reports on "worst case" housing problems and needs for assistance, read Chapter 2 and suggested additions and corrections. Barbara Sard of the Center on Budget and Policy Priorities read Chapter 6 and provided comments on the housing side of the social safety net. She also enlisted her colleagues at the Center to review portions of Chapter 6 on the income side of the safety net: Ed Bolen, Brendan Duke, Chye-Ching Huang, LaDonna Pavetti, Kathleen Ronig, and Chad Stone. We thank them for their comments and for their identification of literature that we had missed"--